Foreign Employment and its Socio-Economic Impacts on Rural People of Nepal: A Study Based on Mahalaxmi Municipality of Lalitpur - Dahal, Ananta Raj (Patan Pragya, 2019)
Foreign employment plays vital role in maintaining the Nepalese’s economy. This paper analyses the nature and socio-economic impacts of the foreign employment in Nepal with reference to Mahalaxmi Municipality of Lalitpur district. Main source of information of this study is primary data and some secondary data are also used for the supplementary usage of the study. Primary data were collected through the direct questionnaire method used the semi-structured for the sample area of people who were selected by judgemental sampling method. Descriptive statistics was used to analyse the data by the help of micro excel program. Major destination for foreign employment is Malaysia and Qatar. Employees who pursue the employment in those countries manage borrowing in interest. They collect the information about employment from brokers, manpower companies and agents. The people of the sample area have made more income from foreign employment than other occupation in local jobs and they spend for food and education. Remittance from the foreign employment has played very positive role to improve school education and better health services of the people of sample area.